ANALYSIS OF MALADAPTIVE BEHAVIORS RESULTING TO NATURAL AND ANTHROPOGENIC HAZARD - Noemi B. Yntig; Lovelyn G. Tipon; Ernyl Henry E. Redula, (The Malaysian Journal of Nursing (MJN), 2019)
Exposure to traumatic stressors and subsequent trauma-related to mental changes may alter a person’s risk-taking behaviour. It is still unclear whether this relationship depends on the specific types of traumatic experiences. Moreover, the association has never been studied in displaced individuals with substantial levels of traumatic experiences. The study determined the factors that could motivate the heterogeneous displaced individual to mal-adaptive behaviours and aimed to analyse the traumatized and displaced individuals having mal-adaptive manifestation. The researcher determined the causes of these maladaptive behaviours and its physical responses exhibited by no less than the respondents who experienced the traumatic events brought about by natural and anthropogenic hazards. This study employed quantitative methods which emphasized on the objective measurements and the statistical, mathematical, or numerical analysis of data that was collected through surveys. Computational techniques were used in determining their mal-adaptive behaviours using the Likert scale. The researcher’s divided the forty (40) individuals which was the subject of the study into two groups. The result showed that the data with the Probability of 0.3 showed using drugs was consistently dominated by the behaviour in Probability (0.1) who are making up excuses as they did not finish the school work and Probability (0.2) which is avoiding conversations with other students. This was probably associated with Internally Displaced Persons curiosity and social media influences. It also showed that the mal-adaptive behaviours exhibit by the respondents was associated by their experiences during traumatic events such as typhoon and or fire hazard.